2018
DOI: 10.4236/ojmi.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Appendicitis in Sub-Saharan Africa

Abstract: Objective: The aim of our study was to propose a solution for rationalizing requests for ultrasound examination and CT scan in suspected acute appendicitis, based on use of the Alvarado score. Patients and Methods: We included in our study all patients consulting for pain of the right iliac fossa, whatever their age and sex, who had been diagnosed with acute appendicitis and who had undergone appendectomy. We used the Alvarado scoring system, based on clinical items and laboratory measurements, to diagnose app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…[34][35][36][37] On the other hand, the percentage of patients who had a score of four and less was smaller in our study compared to other reports. [36][37][38][39] The overall sensitivity of Alvarado score in this study was found to be similar with a result from one systematic review and another report from Morocco but significantly higher when compared to reports from Jordan, Tunisia, and Pakistan. 37,40,[44][45][46] On the other hand, the overall specificity of this score in our study (55.6%) was lower when compared to other reports in which it was in the range of 75-92.3%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[34][35][36][37] On the other hand, the percentage of patients who had a score of four and less was smaller in our study compared to other reports. [36][37][38][39] The overall sensitivity of Alvarado score in this study was found to be similar with a result from one systematic review and another report from Morocco but significantly higher when compared to reports from Jordan, Tunisia, and Pakistan. 37,40,[44][45][46] On the other hand, the overall specificity of this score in our study (55.6%) was lower when compared to other reports in which it was in the range of 75-92.3%.…”
Section: Discussionsupporting
confidence: 87%
“…The predominance of men seen in this study is also reflected in other reports. [36][37][38][39][40][41][42] Our patients were found to be relatively young when compared to other study participants in studies done elsewhere while other scholars reported a comparable mean age with our patients. [38][39][40]42,43 The mean Alvarado score in this study was found to be similar with a study from Qatar while it was higher compared to reports from India and Pakistan.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation